2018
DOI: 10.1002/cncr.31791
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study to assess the safety, tolerability, and pharmacokinetics of CXD101 in patients with advanced cancer

Abstract: BACKGROUND: In the current study, the authors sought to determine the maximum tolerated dose (MTD) of the novel class 1 selective histone deacetylase inhibitor CXD101 in a dose escalation study in patients with advanced solid tumors or recurrent/refractory lymphoma. METHODS: The authors escalated the dose of CXD101 from 1 mg twice daily orally for 5 days in a 21-day cycle (3+3 design). RESULTS: A total of 39 patients were enrolled, 36 of whom received CXD101. Of the 30 patients in the escalation cohort, 29 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…It has been hypothesized that selectively inhibiting class I HDACs could reduce the toxicity, which is brought by off target inhibition on class II HDACs. Preliminary result shows that, PXD101 has lower toxicity and higher tolerability than other non-selective inhibitor (Eyre et al, 2019).…”
Section: Cxd101mentioning
confidence: 89%
“…It has been hypothesized that selectively inhibiting class I HDACs could reduce the toxicity, which is brought by off target inhibition on class II HDACs. Preliminary result shows that, PXD101 has lower toxicity and higher tolerability than other non-selective inhibitor (Eyre et al, 2019).…”
Section: Cxd101mentioning
confidence: 89%
“…Thus, interfering with this process by means of HDAC inhibitors could represent an alternative target, and current HDAC inhibitors might serve as templates for designing new anti-angiogenic/anti-cancer drugs with more potency and selectivity [283]. Clinical trials are underway to test new HDAC derivates in advanced solid tumors and hematologic malignancies [284]. Moreover, new strategies and clinical trials are emerging using HDAC-inhibitors in combination settings to increase their efficacy in various malignancies [281].…”
Section: Future Perspectives—possible Answers To Therapy Resistancementioning
confidence: 99%
“…Immunohistochemical assessment of the HR23B protein, which shuttles ubiquitinated cargo proteins to the proteasome has been shown to correlate with responses to HDIs in CTCL, 46 although initial data in a mixed population of lymphomas and other malignancies expressing high HR23B levels from a Phase I study of the oral HDI CXD101 has not confirmed a clear association between HR23B expression and response. 26…”
Section: T-cell Lymphomamentioning
confidence: 99%
“…85 Epigenetic changes are clearly important in the pathogenesis of HL, 10 and in vitro activity of HDIs has been demonstrated, 44 but relatively few studies have reported efficacy outcomes. Table II 9,26,39,47,97,99 summarises selected published studies. The largest single-agent study examined the oral agent panobinostat in 129 patients with R/R HL after autologous transplant.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
See 1 more Smart Citation